Tindak Pidana Penggelapan yang Bernuansa Tindak Pidana Korupsi - Nimas Ayu Dianing Asih (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Corruption crimes are very vulnerable to being committed by civil servants in connection with their work duties. Apart from that, the element of state financial loss which can result in state financial loss is also important in criminal acts of corruption committed by civil servants. This research was carried out using a descriptive analysis method, namely analyzing the relationship between applicable laws and regulations and the practice of implementing positive law. Embezzlement in office committed by civil servants that falls into the realm of criminal acts of corruption fulfills the elements of an article in the Corruption Eradication Law and must contain the element of